Campur Kode Kebahasaan dalam Lagu â€œJPDAâ€ Krisna Purpa (KIS Band) - Ni Kadek Nita Noviani Pande (Institut Seni Indonesia Denpasar, 2020)
Purpose: The purpose of this study is to describe the form, type, and function of the use of code mixing and the factors that influence the occurrence of code mixing in the lyrics of a Balinese pop song titled â€œJPDAâ€ (Jauh Pandang dari Hati) written by Krisna Purpa in KIS Bandâ€™s album titled Story of Me (2013). Research methods: As a scientific work, this study uses a qualitative research as a base for writing the article.Results and discussion: The use of mixed codes is in the form of words, phrases, baster, word repetition, and clauses, description of the type of inner code-mixing outer code mixing. The factors that influence the occurrence mix the code in the song. Implication: Code mixing is the mixing of elements of a foreign language or regional language into the structure of the main language.